Genetic association analysis of the cardiovascular biomarker: N-terminal fragment of pro-B-type natriuretic peptide (NT-proBNP) - Yang, Yuan; Zmuda, Joseph M.; Wojczynski, Mary K.; Thyagarajan, Bharat; Christensen, Kaare; Cvejkus, Ryan K.; Kuipers, Allison L. (PloS one, 2021)
NT-proBNP is a biomarker of cardiovascular disease (CVD). Little is known about the heritability and genetic variants associated with NT-proBNP. Therefore, we estimated the heritability of and examined genetic associations of SNPs in the BNP gene region with circulating NT-proBNP and prevalent CVD in 4,331 participants from the Long Life Family Study (LLFS). Genotypes of 10 SNPs from the NPPB and NPPA regions that encode BNP and A-type natriuretic peptide, respectively, were tested for association with NT-proBNP and prevalent cardiovascular disease and risk factors. We performed analyses using the Sequential Oligogenic Linkage Analysis (SOLAR) program to account for family relatedness, and adjusted all models for age, sex, and field center. The mean age of the LLFS was 69.8 years (range 24-110) with 55.4% females. NT-proBNP was significantly heritable (h2 = 0.21; P = 4x10-14), and the minor alleles of rs632793 (p<0.001) and rs41300100 (p = 0.05) were independently associated with higher serum NT-proBNP levels. Additionally, the minor allele of rs632793 was significantly and consistently associated with lower prevalent CVD, including blood pressures, independent of NT-proBNP level (all P<0.05). Results for prevalent CVD, but not NT-proBNP levels, showed significant interaction by familial generation. In this family-based study of subjects with exceptional longevity, we identified several allelic variants in the BNP gene region associated with NT-pro-BNP levels and prevalent CVD.